Sistem Pendukung Keputusan Pemilihan Vendor Project Menerapkan Metode Analytical Hierarchy Process (AHP) - Apriyaningsih, Apriyaningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Procurement of goods and services is one of the initial stages in the procurement of a project, including the selection of project vendors. Some of the problems that exist when working on a project such as delays in the provision of spare parts and incompetent experts in project work greatly affect the smooth running of the project. The right vendor selection is one of the keys to the company's success in completing a project. The Analytical Hierarchy Process (AHP) method is a method that can help companies make decisions, especially in the selection of project vendors. From the results of calculations using the Analytical Hierarchy Process (AHP) method for the selection of project vendors based on the main criteria, the most important in selecting project vendors is quality with a weight of 0.36, Vendor B is in first place with a weight of 0.35 or equal to 33.1%, vendor A is in the second position at 0.30 or 27.4%, vendor D is in the third position at 0.18 or 21.4%, the last position is occupied by vendor C at 0.17 or 18.1%